Development of sulfonated chitosan membranes modified with inorganic nanofillers and organic materials for fuel cell applications - Zungu, Nondumiso Petunia (Vaal University of Technology, 2021)
Fuel cell technology is a promising clean energy source compared to internal combustion engines and electricity generating plants which are associated with high emissions of greenhouse gases. The aim of this study was to modify chitosan into polymer electrolyte membranes suitable for use in PEMFC and DMFC fuel cells. Chitosan modification was done with 2-aminoethanesulfonic acid (2-AESA), dimethylformamide (DMF) and silica nanoparticles. The effect of the modification on the properties of the developed chitosan membranes was studied using FTIR, XRD, SEM-EDS and TGA. The performance of the membrane electrode assemblies was investigated. The formation of electrostatic interactions in the developed sulfonated chitosan membranes was confirmed via the Fourier transform infrared (FTIR) analysis, indicating a shift in the wavenumber of the N-H bonds from 1581 cm-1 on the chitosan spectrum to a lower wavenumber of 1532 cm-1 in the FTIR spectra of the membranes and by the new peak at the wavenumber of ~1260 cm-1 attributed to the asymmetric O=S=O stretching vibrations of the sulphate groups and sulfonic acid groups from the cross-linking sulphuric acid solution and 2-aminoethanesulfonic acid incorporated on the chitosan polymer chain during the modification. Notably, the FTIR spectra of the developed sulfonated chitosan membranes lacked the peak at the wavenumber of ~1153 cm-1 attributed to the stretching of C-O-C bonds of the polysaccharide ring of chitosan. A reaction mechanism was proposed in this study illustrating the possible conversion of the polysaccharide rings of chitosan into a poly (cyclohexene-oxide) thermoplastic rings in the developed membranes. The TGA/DTGA results of the developed sulfonated chitosan membranes showed three degradation stages. The initial weight loss occurred at temperatures ˂100 °C due to the evaporation of volatile components and water molecules inside the membranes. The second degradation phase of the membranes occurred at 208 ℃ with a loss in weight of >30% resulting from the decomposition of cross-linking networks. The third degradation stage was associated with the decomposition of the main polymer backbone of the membranes and occurred at 263°C for the chitosan membranes modified with 2-aminoethanesulfonic acid and at 266 °C for the chitosan membrane modified with silica nanofiller. The TGA/DTGA curves of Nafion 117 showed a small loss in weight of ~ 5% before a sharp decomposition that occurred between 346–505 °C. The XRD diffractograms of the developed sulfonated chitosan membranes showed amorphous phases, the crystal peaks of chitosan at 2theta of 10° and 20° were flattened on the membranes. The SEM images showed a homogenous surface morphology for the sulfonated chitosan membrane with a higher weight percentage of 2-aminoethanesulfonic acid (13,6 wt.%). The SEM images performed on the surface of the sulfonated chitosan membrane modified silica nanoparticles showed a slight agglomeration associated with the migration of the unbonded silica to the surface. The methanol permeability coefficient of the developed sulfonated chitosan membrane modified with 2-aminoethanesulfonic acid was calculated to be 2.29x10-6 cm2/s. This value was close to the methanol permeability coefficient of 2.33x10-6 cm2/s associated with unfavourable depolarisation at the cathode in direct methanol fuel cells when using Nafion 117. The proton diffusion coefficient of Nafion 117 was calculated to be 1.64x10-5 cm2/s and that of the developed sulfonated chitosan membrane modified with 2-aminoethanesulfonic acid was found to be 6.56x10-6 cm2/s, respectively. The fuel cell performance of the developed sulfonated chitosan membrane modified with 2AESA was investigated in a hydrogen fuel cell (PEMFC) supplied with H2 and O2 directly from the electrolyser. The sulfonated chitosan membrane modified with 2-aminoethanesulfonic acid (13.6 wt.%) achieved an open-circuit voltage of ~0.9 V and a maximum power output of 64.7 mW/cm2 at a maximum current of 70 mA. The current produced by the developed chitosan membrane was applied into the load and was able to turn (power) the electric fan. The sulfonated chitosan membrane modified with silica nanoparticles (2 wt.%) yielded an open-circuit voltage of ~0.9 V and attained a maximum power output of 58 mW/cm2 at a maximum current output of 60 mA/cm2. The current generated by the membrane was also able to turn the electric fan. The Nafion 117 membrane was also investigated under similar conditions and obtained an open-circuit voltage of 0.6 V and a maximum power output of 130 mW/cm2 at the maximum current output of 308 mA. The current produced by Nafion 117 was supplied into the load and was able to turn the electric fan.
M. Eng. (Department of Chemical Engineering, Faculty of Engineering and Technology), Vaal University of Technology.
Keywords: Sulfonated chitosan membranes; Inorganic nanofillers; Organic materials; Fuel cell technology; Polymer electrolyte membranes; Nanoparticles; Dissertations, Academic -- South Africa.; Nanoparticles.; Polymers.; Fuel cells.